2003
DOI: 10.1097/00007632-200303150-00014
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The results suggest that a region on the X chromosome may be linked to the expression of familial idiopathic scoliosis in a subset of these families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 0 publications
0
28
0
Order By: Relevance
“…Chromosomes previously studied included 6, 9, 12, 16, and 17. Most of the studies regarding genetic influence on AIS were conducted in families: chromosomes 6p (D6S1051–D6S1017), 6q (D6S1053–D6S1021), 8q IS3 (D8S1477–D8S279), 9q (D9S938–D9S934), 10q (D10S1222–D10S212), 16q (D16S764–D16S2624), 17p IS2 (D17S974–D17S1294), 18q (D18S1357–D18S1371), and 19p IS1 (D19S1034) [10111314151718]. Our study was performed in patients who were unrelated, and we found a risk for one marker.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chromosomes previously studied included 6, 9, 12, 16, and 17. Most of the studies regarding genetic influence on AIS were conducted in families: chromosomes 6p (D6S1051–D6S1017), 6q (D6S1053–D6S1021), 8q IS3 (D8S1477–D8S279), 9q (D9S938–D9S934), 10q (D10S1222–D10S212), 16q (D16S764–D16S2624), 17p IS2 (D17S974–D17S1294), 18q (D18S1357–D18S1371), and 19p IS1 (D19S1034) [10111314151718]. Our study was performed in patients who were unrelated, and we found a risk for one marker.…”
Section: Discussionmentioning
confidence: 99%
“…The reported complications of scoliosis surgery are serious [9] and can be avoided in a majority of children with IS if early diagnosis and proper bracing is used. In conservative societies, girls often remain covered, and early spine deformities are easily missed such that most of the affected children end up being treated operatively There is currently no clear con-sensus regarding the genetic influence on scoliosis; however, reports indicate that adolescent IS (AIS) is linked to a few chromosomes [101112131415], and most of these linkages are found to be in familial scoliosis. Heary and Madhavan [16] stated that scoliosis can be inherited because of autosomal dominant, X-linked, or multi-gene influences.…”
Section: Introductionmentioning
confidence: 99%
“…Genome-wide linkage screens and fine-mapping of candidate loci in families with at least two members with IS, termed F amilial I diopathic S coliosis (FIS), have identified candidate regions on 6q, 10q, 18q [3]; 17p11.2 [4]; 19p13.3, 2q [5]; Xq23-26 [6]; 6p25-22, 6q14-16, 9q32-34, 16q11-12, 17p11-q11 [7]; 8q12 [8]; 9q31.2-q34.2, 17q25.4-qtel [9]; and 12pter [10]. Candidate regions on chromosomes 9q32-34, and 19p13 have been independently confirmed [9,11].…”
Section: Introductionmentioning
confidence: 99%
“…Emery and Remoin17 believed that the genetic influence in AIS follows the principles of the Mendelian Inheritance, but Lowe et al18 suggested that there is evidence that AIS is inherited in an autosomal dominant manner. The study by Justice et al8 sheds light on the aspect that there is a possibility of X-linked inheritance in AIS. Scoliosis has long been know to occur in the human race and scientists have yet to determine the exact mode of inheritance.…”
Section: Discussionmentioning
confidence: 99%